Effect of Muscle Strength on Functionality after Shoulder Tendon Transfer in Brachial Plexus Birth Injury: Is There a Relationship between Them? - Zeynep Hoşbay; Gülsena Utku Umut; Müberra Tanrıverdi; Okyar Altaş; Atakan Aydın (Children)
Background/Objectives: Secondary problems in BPBI occur due to decreased muscle strength in the upper extremities. Comprehensive assessment methods are necessary to understand structural problems and to plan appropriate interventions in children with BPBI. We investigated the relationship between distal muscle strength, range of motion (ROM), and functionality by comparing distal muscle strength on the affected and unaffected sides in patients with BPBI who underwent shoulder tendon transfer. Methods: A total of 25 children with BPBI, 13 (52%) girls and 12 (48%) boys, aged 4–7 years (mean age: 5.98 ± 1.27 years), who had undergone shoulder tendon transfer surgery at least one year prior to the study were included. The muscle strength of the elbow, forearm, and wrist were assessed using the MicroFET®2 Digital Hand Dynamometer. The ROM of the elbow, forearm, and wrist were measured using the universal goniometer. The Pediatric Evaluation of Disability Inventory (PEDI) was used for functionality assessment. Results: The strength of the elbow flexor–extensor, forearm pronator–supinator, and wrist extensor muscles on the affected side was greater than on the unaffected side in all children (p < 0.001). No correlation was found between muscle strength, ROM, and functionality in the affected extremity (p > 0.005). Conclusions: Although children with BPBI have good shoulder function after shoulder tendon transfer, structural problems in the distal joints may affect their functionality during daily life. Distal joint strengthening and ROM exercises, as well as bimanual functional activities, should be included in the rehabilitation programs of children with BPBI after shoulder tendon transfer.